Oral Copus for Reference of Contemporary Spanish - Språkbanken Text (University of Gothenburg, 2024)
Compiled between January 1991 and February 1992 at the Universidad Autónoma de Madrid (UAM) under the leadership of Dr. Francisco Marcos Marín. It contains transcriptions of recorded audio tapes of a varied nature (private conversations, lectures, radio and television programmes, etc.). This corpus is part of SOL - Spanish Online.

Korpusen sammanställdes mellan januari 1991 och februari 1992 vid Universidad Autónoma de Madrid (UAM) under ledningen av Dr. Francisco Marcos Marín. Texterna innehåller transkriptioner av inspelade ljudband av varierande karaktär (privata samtal, undervisning, radio- och tv-program, etc.). Korpusen ingår i samlingen SOL - Spanska Online.
Corpus Oral de Referencia del Español Contemporáneo
Keywords: Language Technology (Computational Linguistics); transcription; Spanish; 1990s; corpus; Natural Language Processing; Språkbehandling och datorlingvistik